PRESENCE OF THE EXCHANGEABLE ALUMINIUM IN LOWLAND SOILS COLLECTED IN THE MARANHÃO STATE - Silva, Alessandro Costa da (Ciência e Natura, 2014)
http://dx.doi.org/10.5902/2179460X13423 The lowlands region of the Maranhão state includes soils with high fertility and a large agricultural potential. However, there is no adequate management systems to increase crop productivity and soil quality. This work aimed to characterizes chemically four soils (Vertisoils) collected in the region, and to compare with to the soil control (Oxisoil). In the greenhouse conditions, the maize growth under the five soils was observed. Higher nutrients and aluminium levels compared to the control were observed. At the same time, higher root growth in plants was verified, common situation for plant cultivated under soils with low aluminium levels. Important remember that even presented high aluminium levels (in four soils), the plant growth was not affected. This can be explained by calcium and magnesium presence which inhibit aluminium toxicity in the plants.